2009
DOI: 10.1038/modpathol.2008.196
|View full text |Cite
|
Sign up to set email alerts
|

The role of Movat pentachrome stain and immunoglobulin G4 immunostaining in the diagnosis of autoimmune pancreatitis

Abstract: Autoimmune pancreatitis is highly responsive to steroid therapy, but because it mimics pancreatic cancer, it often precipitates unnecessary surgery. Adequate diagnostic tests are needed to permit appropriate medical therapy. Lymphocytic and obliterative phlebitis are reported in the majority of cases, as are elevated IgG4-positive plasma cells, indicating their high sensitivity. Their specificities, especially when used in conjunction, however, remain largely unknown. Movat pentachrome vascular and IgG4 immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…A previous report comparing pancreatic biopsy specimens and surgically resected specimens showed that pancreatic specimens by core biopsy provided adequate histologic findings for AIP in only 22% of cases (2/9), whereas surgical specimens almost always provided sufficient findings for making a diagnosis [34]. In addition, the patchy distribution of specific histological findings, such as LPSP [35][36][37] and infiltration of IgG4-positive plasma cells [38] and the different severities [34] can affect the detection rate of histological findings. These data indicate that 22-gauge Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A previous report comparing pancreatic biopsy specimens and surgically resected specimens showed that pancreatic specimens by core biopsy provided adequate histologic findings for AIP in only 22% of cases (2/9), whereas surgical specimens almost always provided sufficient findings for making a diagnosis [34]. In addition, the patchy distribution of specific histological findings, such as LPSP [35][36][37] and infiltration of IgG4-positive plasma cells [38] and the different severities [34] can affect the detection rate of histological findings. These data indicate that 22-gauge Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of the studied markers was evaluated independently by two independent observers (ZD, JD) using the Leica LD 5000HL light microscope. Identification of tissue types was based on colour evaluation of stained tissues derived from the available literature (Chu et al 2009;Felföldi et al 2021;Kajbafzadeh et al 2017;Willershausen et al 2019), Due to the small size of the material, statistical analysis was omitted and the results were presented as observational data.…”
Section: Methodsmentioning
confidence: 99%
“…Immunochemical staining for IgG4 (monoclonal anti-mouse IgG4 antibody, Binding Site, Birmingham, UK) was conducted with 4 μm-thick paraffin embedded tissue sections, as described previously. 15 Briefly, antigen was retrieved by heating the tissue sections in pH 6.0 citrate buffer. Tissue sections were then incubated with primary anti-mouse IgG4 (1 : 400) for 37 minutes at 37°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%